Relative Sea-Level Change in the Northern Strait of Georgia, British Columbia - James, Thomas; Hutchinson, Ian; Vaughn Barrie, J.; Conway, Kim; Mathews, Darcy (Géographie physique et Quaternaire, 2005)
AbstractTwenty-four new radiocarbon dates from isolation basin cores, excavations and natural exposures, and an archeological site, constrain relative sea-level change since the last glaciation in the northern Strait of Georgia, British Columbia. Relative sea level fell rapidly from about 150 m elevation to 45 m elevation from 11 750 to 11 000 BP (13 750 to 13 000 cal BP), then its rate of fall slowed. The initial rapid emergence began soon after the transition from proximal to distal glaciomarine sedimentation, when the glacial front retreated from the Strait of Georgia and the Earth’s surface was unloaded. A sea-level lowstand a few metres below present-day sea level may have occurred in the early Holocene, but sea level was near its present level by 2000 BP. Sea-level change in the northern Strait of Georgia lagged the mid Strait of Georgia, 80 km to the south, by a few hundred years during initial emergence. The lowstand in the northern strait was later and probably shallower than in the mid strait. Isostatic depression inferred from the sea-level observations can be fit with two decaying exponential terms with characteristic decay times of 500 and 2600 years. The faster decay time corresponds to a shallow mantle viscosity of about 1019 Pa s, consistent with previous glacio-isostatic modelling. The present-day crustal uplift rate from the residual isostatic effects of the Cordilleran Ice Sheet is about 0.25 mm/a. Crustal uplift is not expected to significantly ameliorate projected sea-level rise in the mid and northern Strait of Georgia because present-day vertical crustal movements are inferred to be small.